Primary Ewing's sarcoma of the jejunum presenting as sepsis - Hsiang-Jung Chen; Hong-Ming Chao; Junn-Liang Chang; Yen-Lin Chen; Chih-Chien Yen (Formosan Journal of Surgery, 2020)
Extraosseous Ewing's sarcoma (ES), also referred to as extraskeletal ES, is a rare tumor of primitive cells that occurs in children, adolescents, and young adults. This tumor mainly involves the soft tissue of the extremities and thorax. We report a case of extraskeletal ES of the jejunum without associated skeletal location. A 26-year-old woman with no medical history presented to the emergency department with a 3-day history of a fever along with nausea, vomiting, and abdominal pain. An abdominal contrast computed tomography scan revealed a homogeneous bowel mass size 8.5 cm × 4.3 cm × 6.1 cm in the lower abdomen with invasion of the ileum is noted. Extraluminal free air and abscess formation size 10.6 cm × 5.2 cm × 8.3 cm is noted, suggestive of bowel perforation. After the surgery, the specimen was sent to the pathology department for examination. We received one segmental jejunum (25 cm in length and 6 cm in diameter of the lumen) that weighed 450 g in total. Sections revealed an ill-ulcerative mass measuring 6 cm × 4 cm × 0.5 cm with gray-to-brown coloration and extensive necrosis with perforation; the mass was located 15 and 7 cm in length from the bilateral cut ends. In addition, focal vascular proliferation, and infiltrate deeply to the serosa with mesenteric enlarged lymph nodes were observed. Furthermore, the mesenteric regional lymph nodes show metastatic sarcoma. The definitive diagnosis was based on the findings of histomorphology, immunohistochemistry, and molecular pathology.